Pengembangan Aplikasi Presensi Menggunakan Model Waterfall - Nifa Abdillah, Muhamad Hafidz; Pambudi, Naufal; Julian, Risma; Bahri, Syaiful; Saifudin, Aries (shofanah Media Berkah, 2024)
Monitoring attendance or presence in an agency has a very important role. An attendance list that is organized, neat, and always updated is crucial. The Covid-19 pandemic situation has affected the working hours of employees, students, and college students with a reduction in working time and a division between working from the office (WFO) or working from home (WFH). In addition, students and college students also carry out learning activities from home. However, attendance must still be taken as it has significant value. The attendance system that requires physical presence at the workplace needs to be replaced with a new, more flexible online system. With this system, attendance can be done both at the office and at home according to the predetermined WFO or WFH schedule. In developing this Presence Application, the software development method used is the Waterfall method. The Waterfall method was chosen because it prioritizes the quality of the application rather than considering schedule and cost.